SrrB, a Pseudo-Receptor Protein, Acts as a Negative Regulator for Lankacidin and Lankamycin Production in Streptomyces rochei - Misaki, Yuya; Yamamoto, Shouji; Suzuki, Toshihiro; Iwakuni, Miyuki; Sasaki, Hiroaki; Takahashi, Yuzuru; Inada, Kuninobu; Kinashi, Haruyasu; Arakawa, Kenji (Frontiers in Microbiology, 2020)
Streptomyces rochei 7434AN4, a producer of lankacidin (LC) and lankamycin (LM), carries many regulatory genes including a biosynthesis gene for signaling molecules SRBs (srrX), an SRB receptor gene (srrA), and a SARP (Streptomyces antibiotics regulatory protein) family activator gene (srrY). Our previous study revealed that the main regulatory cascade goes from srrX through srrA to srrY, leading to LC production, whereas srrY further regulates a second SARP gene srrZ to synthesize LM. In this study we extensively investigated the function of srrB , a pseudo-receptor gene, by analyzing antibiotic production and transcription. Metabolite analysis showed that the srrB mutation increased both LC and LM production over four-folds. Transcription, gel shift, and DNase I footprinting experiments revealed that srrB and srrY are expressed under the SRB/SrrA regulatory system, and at the later stage, SrrB represses srrY expression by binding to the promoter region of srrY. These findings confirmed that SrrB acts as a negative regulator of the activator gene srrY to control LC and LM production at the later stage of fermentation in S. rochei.